2022
DOI: 10.3390/en15134913
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Evaluation of the Efficiencies of Metal-Free 1,3,4-Oxadiazole Dye-Sensitized Solar Cells: Insights from Electron–Hole Separation Distance Analysis

Abstract: Herein, some novel metal-free 1,3,4-oxadiazole compounds O1–O7 were evaluated for their photovoltaic properties using density functional theory (DFT) and time-dependent density functional theory (TD-DFT) calculations to determine if they can serve as metal-free organic dyes in the use of dye-sensitized solar cells (DSSCs). To understand the trends in the relative efficiencies of the investigated compounds as dyes in DSSCs, their electron contributions, hole contributions, and electron–hole overlaps for each re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…92 A study by Bulat et al , debunked previous studies that suggested that an electron that occupies the HOMO level will automatically be excited to the LUMO level as this study revealed that an electron's position in atomic space and the contour of the molecule also play a role in excitations. 93 Nevertheless, it is still widely accepted that HOMO–LUMO energy gaps play a significant role in electron excitations. 94 Comparing the ligand to the complexes, we observe greater stability, larger IP, lower EA, larger η , lower δ and ω indices in the former.…”
Section: Resultsmentioning
confidence: 99%
“…92 A study by Bulat et al , debunked previous studies that suggested that an electron that occupies the HOMO level will automatically be excited to the LUMO level as this study revealed that an electron's position in atomic space and the contour of the molecule also play a role in excitations. 93 Nevertheless, it is still widely accepted that HOMO–LUMO energy gaps play a significant role in electron excitations. 94 Comparing the ligand to the complexes, we observe greater stability, larger IP, lower EA, larger η , lower δ and ω indices in the former.…”
Section: Resultsmentioning
confidence: 99%
“…The perovskite regeneration process is related to Gibbs energy change of the hole transport from the perovskite to the HTM and can be expressed by Equation () [45]. ΔGregperovskite=normalEOXperovskitnormalEHOMOHTM …”
Section: Computational Bachgroundmentioning
confidence: 99%